Takotsubo syndrome following mitral transcatheter edge-to-edge repair: a case report and literature review - Pang, Si; Huang, Haobo; Zhu, Yunlong; Zhou, Rong; Tan, Dan; Zhang, Yuqing; Wu, Mingxing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTakotsubo syndrome (TTS), characterized by transient wall motion aberrations and clinical manifestations akin to acute coronary syndrome, predominantly arises from significant physical or emotional stress, often throughout the perioperative period. The prevalence and mechanisms of this condition remain inadequately elucidated, particularly in the context of transcatheter valvular disease procedures. This knowledge gap may result in under-recognition and subsequent delays in diagnosis.Case summaryA 76-year-old female was scheduled in our department for mitral transcatheter edge-to-edge repair (TEER). Despite the procedural success, multi-lead T-wave inversions and a 43% decrease in ejection fraction accompanied by new apical hypokinesis were noted postoperatively. Subsequent assessment revealed TTS. After receiving the optimal medical therapy, the patient was discharged after 10 days without experiencing acute chest pain or shortness of breath. The patient’s electrocardiogram (ECG) and function of the left ventricular function, particularly regional wall motion abnormalities, recovered on the 20th day after surgery.DiscussionThe limited literature reporting TTS post-TEER that we reviewed suggests that this rare complication must be anticipated in patients exhibiting an unexpected postoperative ECG and impaired myocardial contraction.ConclusionResearchers call for high-risk patient identification, adequate preoperative evaluation, and vigilant postoperative monitoring, and note the significance of early detection in optimizing therapeutic outcomes. Further research is imperative to further explore the management and prognosis of TTS following TEER.